Teoretycznoprawne aspekty wykluczenia społecznego - Blicharz, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The multidimensional and dynamic nature of social exclusion requires (an) adequate tool(s) for regulating the course of monitoring and eliminating causes of preventive action. It requires integrated actions which take into account the relevant social, economic, and political factors generating exclusion.
Keywords: social exclusion; poverty; social economy; social reintegration; professional reintegration